Evaluasi Pelayanan Publik Di Dinas Lingkungan Hidup Kabupaten Bima Dalam Pengelolaan Sampah Di Tempat Pembuangan Akhir (TPA) (Studi Pada Dinas Lingkungan Hidup Kabupaten Bima) - Sri Asmiatiningsih (Universitas 17 Agustus 1945 Semarang, 2023)
The purpose of this research is to evaluate the public services available at the Bima Regency Environmental Service in waste management at the Final Disposal Site (TPA). In this study, researchers used descriptive research with a qualitative approach. While the location of this research was carried out at the Bima Regency Environmental Service. The types and sources of data in this study are primary data and secondary data. The results of this study indicate that the quality of public services at the Environmental Service is optimal, although it is still hindered by several obstacles related to waste management. The supporting factors such as the performance of employees in providing services, as well as inhibiting factors such as the geographical location of the Bima Regency area, and the lack of availability of land, lack of communication from the Office related to the community, lack of outreach to the community. It can be interpreted that the Quality of Public Services at the Environmental Office for Waste Management at the TPA is maximal enough in providing its services.